2008
DOI: 10.2527/jas.2007-0335
|View full text |Cite
|
Sign up to set email alerts
|

Induction of milk ejection and milk removal in different production systems1

Abstract: Milk ejection is important during milking or suckling to obtain the alveolar milk fraction, which can represent more than 80% of the milk stored in the udder of dairy cows. In response to tactile teat stimulation, either manually or by the milking machine, milk ejection is induced by the release of oxytocin and resultant myoepithelial contraction. The time from the start of tactile stimulation until the occurrence of milk ejection spans 40 s to > 2 min and increases with a decreasing degree of udder filling. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 53 publications
2
49
0
3
Order By: Relevance
“…Such an increase could be related to the requirement for prolactin (in association with insulin and cortisol) for initiation of milk secretion in the periparturient period (Tucker, 2000). Moreover, frequent and intensive suckling play a role in maintaining lactation, primarily via stimulation of oxytocin release, but also provoking secretion of prolactin, vasopressin, ACTH and cortisol (Bruckmaier and Wellnitz, 2008;Olsson and Högberg, 2009). This is consistent with the observation of elevated cortisol concentrations in lactating primiparous females at early lactation (group 2) compared with nulliparous females (group 1) in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Such an increase could be related to the requirement for prolactin (in association with insulin and cortisol) for initiation of milk secretion in the periparturient period (Tucker, 2000). Moreover, frequent and intensive suckling play a role in maintaining lactation, primarily via stimulation of oxytocin release, but also provoking secretion of prolactin, vasopressin, ACTH and cortisol (Bruckmaier and Wellnitz, 2008;Olsson and Högberg, 2009). This is consistent with the observation of elevated cortisol concentrations in lactating primiparous females at early lactation (group 2) compared with nulliparous females (group 1) in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that emotional stress may stimulate endogenous opioids release which in Table 3 Effect of suckling management on milk flow characteristics, udder health, BCS, and interval from calving to first postpartum ovulation of cows. turn may block oxytocin secretion and milk ejection (Bruckmaier and Wellnitz, 2008). Indeed, administration of the opioid morphine inhibited oxytocin release in dairy cows, while administration of an opioid antagonist restored normal secretion (Tanĉin et al, 2000), but how endogenous opioids mediate these effects is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, no differences existed in cortisol response to an ACTH stimulation test between competition index categories (by dividing the number of times the cow displaced another at the feed bunk by the total number of displacements the cow was involved in, either as an actor or reactor) in Holstein dairy cattle [113]. Of interest, susceptibility of individual cows to the inhibition of oxytocin release and milk ejection can be predicted by an ACTH challenge test [114,115]. Cortisol concentrations did not differ in dairy cows between animals in social isolation compared with animals deprived of lying down both in the baseline series and after ACTH administration [116].…”
Section: Adrenocorticotropic Hormone Challenge Testmentioning
confidence: 98%